Violence against women : towards formulating an enforceable legal regime in Nigeria - Umar, Mohammed Amin (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2018)
This dissertation examines the commitment of Nigeria in eradicating violence against women in its entire ramification. Successive Nigerian governments have acceded to all international and regional instruments on human rights and particularly on women's human rights and empowerment. Towards this end the Constitution of Federal Republic of Nigeria 1999 elaborated provision on civil and political rights and also on economic, social and cultural rights as a solemn textual declaration. These provisions are quite significant due to the supreme status of the constitution and its prevail over all laws in Nigeria. Thus Nigeria has enacted the Violence Against Persons (Prohibition) Act 2015 in its bid to eradicate all forms of violence against women and guarantee their rights. This legislation is undermined by identified and defined shortcomings which include inadequacy of necessary provisions, restricted jurisdiction and applications that are crucially not national legislation. This study therefore seeks to investigate why violence against women in Nigeria persists and existing legal and institutional framework responses have failed to curtail the rising profile of violence against women. This study also emphasise that there is need for other necessary legislations to be promulgated and the existing one's amended. Accordingly there is need to establish a dedicated government agency to combat violence against women in Nigeria. Otherwise it will be far from realising its international and regional obligations. This research adopted the qualitative methodology and employed doctrinal and non-doctrinal approaches in order to realise it objectives. Hence unstructured and semi-structured interview were administered and the respondents were selected based on purposive random sampling. Thus, judges, policy makers, legislators, traditional rulers, law enforcement agents and women/victims/survivors of violence were interviewed. The responses received have contributed immensely toward conclusive evaluation of this research culminating in to a few suggestions. This research persistently maintained that in order for Nigeria to formulate an enforceable legal regime in eradicating violence against women, the suggestions on law reform in both amendment and enactment is quite imperative.